My day by day life with an ostomy: the patient influencer on Instagram - Martín García, Alberto (2024)
This study focuses on ostomy, a digestive surgery that has increased in recent years. Its limited visibility and low awareness among the population leads us to investigate the way it is represented on social media and the role played by certain content creators on Instagram. Using a methodology based on content analysis, we examine a sample of Instagram profiles focused on the visibility of this surgery. The results reveal that the existence of these profiles and their regular publication of content about ostomy: 1) It causes a reassuring effect for people who are in a similar or close situation; 2) The fact of relating their experience and naturally showing their day-to-day life with “pouch” helps to raise awareness of a situation that is irreversible in many cases, but which allows improving the quality of life of many patients with serious intestinal diseases; and 3) Their role as content creators and their effect on the ostomy population brings them closer to the role of influencers with direct and close contact with the target audience.